2017
DOI: 10.5267/j.dsl.2016.6.003
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid approach based on ANP, ELECTRE and SIMANP metaheuristic method for outsourcing manufacturing procedures according to supply chain risks - Case study: A medical equipment manufacturer company in Iran

Abstract: Nowadays enterprises should consider seeking to reduce the supply chain risks as a crucial part of their activities in order to improve their competitiveness in the international context. Choosing the suitable strategy in connection with assigning some parts of the production process to outside the organization is a complex multi-criteria decision making problem and it gets more complicated when supply chain risk factors as the factors to select the strategy as well as dependence and the close ties between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…Criteria weighting methods generally include AHP, ANP, BWM, and the methods based on them (Ajrina et al, 2018). Despite being widely used in various fields, AHP and ANP require a great number of comparisons (Farughi & Mostafayi, 2017). On the other hand, BWM has fewer comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Criteria weighting methods generally include AHP, ANP, BWM, and the methods based on them (Ajrina et al, 2018). Despite being widely used in various fields, AHP and ANP require a great number of comparisons (Farughi & Mostafayi, 2017). On the other hand, BWM has fewer comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…(1) ANP allows to show the interaction between the selection criteria at a good level and with a high accuracy compared to the direct method (Abbate et al, 2023;Farughi and Mostafayi, 2017), in our case the most relevant barriers and pathways. While ELECTRE permits to obtain the superiority of the alternatives, to rank the barriers and the corresponding pathways, in order to select the best barriers/pathways.…”
Section: A Hybrid Framework Combining Anp and Electre Imentioning
confidence: 99%
“…So far, very few research studies have dealt with Agri-food supply chain from the perspective of barriers and pathways towards greening an Agri-food supply chain. On the other hand, only few studies have reported a hybrid method (Farughi and Mostafayi, 2017;€ Ozt€ urk et al, 2018), even though the combination of the two methods ANP and ELECTRE allows to eliminate the weak alternatives and help in selecting the best alternative from the available (Farughi and Mostafayi, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the networked organizations, the outsourcing firms can transform themselves into more flexible and agile organizational structures [6,7]. For these reasons, an increasing number of firms have adopted outsourcing strategies, seeking enhanced efficiency and competitiveness, and a topic of strategic outsourcing is increasingly widespread among modern organizations, thereby attracting great interest from organizational scholars, as well as firm management [3,6,[8][9][10]. According to Transaction Cost Economics (TCE), the costs associated with economic exchange play a leading role in the outsourcing decision, and the transactions are made through the governance form requesting minimum costs [11,12].…”
Section: Introductionmentioning
confidence: 99%